(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The integration of polymer additives into bitumen has significantly enhanced the performance and durability of road pavements. This article explores the preparation methods, chemical interactions, and benefits of reinforced polymer-bitumen compositions in road construction. By examining various polymer types and their effects on bitumen properties, the study aims to provide insights into the development of high-performance road materials.